Exploring Stigma by Association among Front-Line Care Providers Serving Sex Workers - Phillips, Rachel (Healthc Policy, 2013)
Stigma by association, also referred to as “courtesy stigma,” involves public disapproval evoked as a consequence of associating with stigmatized persons. While a small number of sociological studies have shown how stigma by association limits the social support and social opportunities available to family members, there is a paucity of research examining this phenomenon among the large network of persons who provide health and social services to stigmatized groups. This paper presents results from a primarily qualitative study of the work-place experiences of a purposive sample of staff from an organization providing services to sex workers. The findings suggest that stigma by association has an impact on staff health because it shapes both the workplace environment as well as staff perceptions of others' support. At the same time, it is evident that some staff, owing to their more advantaged social location, are better able to manage courtesy stigma than others.